Emerging Practices In Community Development Agreements - Loutit, Jennifer; Mandelbaum, Jacqueline; Szoke-Burke, Sam (Journal of Sustainable Development Law and Policy, 2025)
Community Development Agreements (CDAs) have the potential to facilitatethe delivery of tangible benefits from large-scale investment projects, such asmines or forestry concessions, to affected persons and communities. To beeffective, however, CDAs must be adapted to the local context, meaning thatno single model agreement or process will be appropriate in every situation.Nonetheless, leading practices are emerging which can be required bygovernments, voluntarily adopted by companies, and demanded bycommunities. These practices are grounded in ensuring that all parties aresufficiently informed, capacitated, and prepared to engage in meaningfulnegotiations regarding how the investor’s operations should benefit localstakeholders. This article reviews existing research on CDAs, as well asavailable agreements from the extractive sector in Australia, Canada, Laos,Papua New Guinea, Ghana and Greenland. It articulates seven broad leadingpractices and how different stakeholders could work to achieve more effectiveagreements.